THE CAUCASUS AND ADJACENT REGIONS IN THE COSMOGRAPHY OF FAKHR-I MODABBER - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2023)
Among the Muslim texts of the first half of the XIII century, one should highlight the narrative known to researchers as «Shajarai-e ansab-e Mobarakshah-i» («The Tree of the genealogies of Mubarak Shah») or «Bahr al-ansab» («The Sea of genealogies»). This work belongs to the pen of a Persian historian of the late XII – first half of the XIII century. Muhammad ibn Mansur ibn Sa’id or Fakhr-i Moddabir (Mubarak Shah). After the publication of the Persian text of this source, carried out in the first half of the XX century. By Edward Denison Ross, scientists have paid close attention to this work itself, as well as to the biography of its author. However, the most significant attention was focused on those sections of «Bahr al-ansab», where the author described the nomadic Turkic tribes of Desht-i Qipchak, as well as those where Fakhr-i Moddabir outlined the history of the Muslim dynasties that ruled in northern India. Much less attention was paid by specialists to the initial section of the introduction to «Bahr al-Ansab», in which the author proposed cosmography or a description of the world known to people at that time around them. For our part, I would like to understand first of all how, in the author’s opinion, this world was arranged, into which regions it was divided, and what place the Caucasus and adjacent lands occupied in it. Here I would like to draw attention to what toponyms associated with the Caucasus Fakhr-i Moddabir mentions and what he reports about them. An equally important task of this study will be to identify the connections of this part of the text «Bahr al-Ansab» with earlier monuments of Muslim geographical and historical literature, which will make it possible to identify borrowings, but also independent reports of Fakhr-i Moddabir regarding the structure of the world known to mankind at that time. The main results of the study should include a direct indication by the author of «Bahr al-Ansab» to include the Caucasus in the fifth climate, which only partially correlates with the established Muslim tradition of «climatic division» of the surrounding world. An analysis of this part of the work of Fakhr-i Modabber allows us to conclude that, in general, his story about climates lies in the field of tradition laid down by Abu Rayhan Muhammad ibn Ahmad al-Biruni, however, some details of the narrative make us think about what other sources the author of «Bahr al-Ansab» could rely on.